Sistema para el control del cumplimiento del Proyecto Educativo en la Enseñanza Superior Cubana - Baquero-Hernández, Lionel Rodolfo; Mendoza-Peña, Dayana; Rodriguez-Valdés, Osviel; Hernández-González, Bernardo (Revista Científica, 2016)
As part of the training of Cuban university students involved educational project that requires proper control of compliance. At the University of Information Science, is done through a digital model developed by the professor of the group which generates poor control and directly undermines the quality of the process. In this work the solution to the problem as basis of computerization, using OpenUP development methodology, programming language Java Script on the NetBeans platform version 8.0 as Integrated Development Environment, with ExtJS 3.4 framework is detailed, with version 8.0 of the Software Engineering tools Computer Assisted Visual Paradigm for modeling and PostgreSQL 9.3 as a management system database. The system also generates the associated compliance status of the activities that make up the educational project of a group, which facilitates the control and decision making reports.